2016
DOI: 10.15406/jdhodt.2016.04.00116
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Assessment of Gonial Angle by Both Hemispheres of Panoramic Images and Its Comparison with Lateral Cephalometric Radiographic Measurements

Abstract: Background: One of the most important values in cephalometric tracing is the gonial angle which is used to measure growth pattern of patients, teeth extraction pattern in Class II patients, surgical decision in class III skeletal base patients and age estimation in forensic medicine. Gonial angle measured from panoramic radiograph is found to be more reliable than lateral cephalometric radiograph. In the latter, superimposition of the left and right sides angle, makes it difficult to measure accurately gonial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…One of the main advantages of orthopantomogram is that there are no super impositions 8 . Orthopantomogram also shows both hemispheres of mandible and both gonial angle can be compared for any underlying pathological condition like condylar hyperplasia and condylar elongation 10 . Studies that observed the role of panoramic radiographs as a means of examining maxillary and mandibular relationships are lacking in orthodontic literature.…”
Section: Panoramic Radiography Was Invented By Profmentioning
confidence: 99%
“…One of the main advantages of orthopantomogram is that there are no super impositions 8 . Orthopantomogram also shows both hemispheres of mandible and both gonial angle can be compared for any underlying pathological condition like condylar hyperplasia and condylar elongation 10 . Studies that observed the role of panoramic radiographs as a means of examining maxillary and mandibular relationships are lacking in orthodontic literature.…”
Section: Panoramic Radiography Was Invented By Profmentioning
confidence: 99%
“…In Class III individuals , the gonial angle could influence therapy options and assist determine whether surgery is necessary [9,10]. While Kundi.et al [11] claimed that panoramic radiography may detect gonial angle in place of truthfully as a lateral cephalogram, Shahabi.et al [12] recommended foremost lateral cephalogram to estimate gonial angle. Additionally, several researchers discovered significant individual differences in gonial angle alteration, which had been influenced by age in addition of different forms of malocclusion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is a constantly changing anatomical landmark in the head which can be measured clinically or radiographically. 3,4 Patient requiring an orthodontic treatment, and jaw surgeries are often subjected to extraoral radiographic investigations which includes panoramic adiography and lateral cephalogram. These radiographs can be used to evaluate the gonial angle easily by using modern digital software.…”
Section: Introductionmentioning
confidence: 99%
“…It is a constantly changing anatomical landmark in the head which can be measured clinically or radiographically. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%